Characterization of an eco-friendly active packaging film for food with ultraviolet light blocking ability - LI, Mi; ZHANG, Yunge; LI, Lewen; XIE, Yunfei; YAO, Weirong; CHEN, Qingmin; JU, Jian (Food Science and Technology, 2023)
An eco-friendly active packaging film for food with ultraviolet (UV) light blocking ability was prepared using nano-magnesium oxide (MgO), nano-zinc oxide (ZnO), nano-cellulose (NCC), and poly(lactic acid) (PLA). The results revealed that the four nanomaterials were evenly dispersed in the PLA films, but no chemical bonds formed according to infrared spectroscopy and scanning electron microscopy. Compared with other PLA films, the PLA films with ZnO were endowed with excellent UV absorption and its surface hydrophilicity was decreased. On the contrary, the PLA films with MgO, ZnO, and NCC had improved mechanical strength, better antimicrobial activity, lower oxygen permeability (OP), and water vapor permeability (WVP). The PLA film with nanoparticles is an excellent active packaging material with improved physical, mechanical, and barrier properties, which can also avoid the damage of food or active ingredients in packaging from UV radiation, and has a broad application prospect for the preparation of multilayered composite active packaging materials for food.